The global threat of race in the decomposition of struggle. Issue 2 (2nd April 2020) - Al-Bulushi, Yousuf
ABSTRACT: Many of the struggles that emerged in the wake of the 2008 global economic crisis eventually experienced decomposition in the face of multiple internal and external threats. While movement composition and decomposition are inevitable in the natural cycle of popular struggles, this article argues that what David Theo Goldberg has termed "the threat of race" constituted one important factor that brought about the eventual demise of these popular mobilizations. By drawing on the cases of US Occupy Wall Street, European anti-austerity protests, and South African struggles against xenophobia, it points to global continuity in anti-blackness across disparate geographies. As these same regions currently confront the threat of righting authoritarianism, this article argues we must also take a self-reflexive look at the seeds of reaction embedded in otherwise progressive and left-wing formations in order to achieve a more sobering account of our present predicament.